COMPARISON OF THE IMPLEMENTATION OF ANIMAL WELFARE IN BROILER CHICKEN FARM IN PUHU AND PERING VILLAGE IN GIANYAR DISTRICT - Akbar Maulana, Dewa; Kadek Karang Agustina; Ketut Tono Pasek Gelgel; I Made Sukada (Buletin Veteriner Udayana, 2024)
Meat demand in Indonesia is mostly supplied by poultry, especially broiler chickens. In order to optimise the supply of broiler chickens, many farmers try to optimise production management to ignore the concept of animal welfare, one of which is by increasing the population in the hope of minimising the movement or activity of the chicken itself so that the energy in the chicken is not used up to move and can be channelled into its growth, this certainly causes violations of the animal welfare aspect itself. This research aims to study the application of animal welfare and its comparison between Puhu and Pering villages. This study used observational method with total sampling, where all broiler farmers in Puhu and Pering villages were recorded. Data collection was done by direct interview guided by an integrated questionnaire on 5 aspects of animal welfare implementation. Data were scored using a Guttman scale and analysed using descriptive qualitative method, and Mann-Whitney test was used to differentiate the application between the two villages. The results of the study found that in Puhu village, 83.3% of farms were in the good category and 16.7% were very good, while in Pering village, 100% of broiler farms were found to apply the concept of animal welfare very well. In the comparison test, it was found that there was a difference in the aspect of fulfilling the principle of freedom from pain or disease, where farmers in Pering village implemented it very well. It can be concluded that there is a very significant difference between the application of animal welfare in broiler chickens in Puhu and Pering villages. It is expected that farmers in Puhu village pay more attention to the health aspects of their livestock so that broiler welfare is more optimal.